Long-Term Assets Exercises I - eBooks and textbooks from bookboon.com - Walther, Larry M. (bookboon.com, 2016)
This exercise book is the first of three exercise books that correspond directly with the Long-Term Assets textbook. The exercises relate specifically to Part 1 of the Long-Term Assets textbook. Exercises cover available for sale and held to maturity securities, balance sheet presentation, investment purchases at par, purchases at a premium, and purchases at a discount. The exercises also cover accounting for equity investments.